COI Metabarcoding as a Novel Approach for Assessing the Honey Bee Source of European Honey - dos Santos Honrado, Mónica Gabriela (2025)
Honey is a widely consumed food product frequently subjected to adulteration, with the mislabeling of its botanical or geographical origin being one of the most common practices. Determining the entomological origin of honey is particularly challenging but of high relevance for ensuring its authenticity, especially for products with protected designation of origin (PDO) labels. This study presents a novel DNA metabarcoding approach targeting a highly informative 406 bp fragment of the cytochrome c oxidase I (COI) gene to differentiate among the three major mitochondrial lineages (A, M, and C) of honey bees (Apis mellifera L.) native to Europe. The target region was selected based on the calculated fixation index (FST), which is frequently used in Population Genetics as a measure of differentiation between populations. The approach was validated with 11 honey samples of known entomological origin and applied to 44 commercial honeys from 13 countries. The approach demonstrated high sensitivity, accurately identifying the entomological origin of honey, including samples produced by honey bees of varying ancestries, which could not be resolved by previous methods based on real-time PCR coupled with high-resolution melting (PCR-HRM) analysis. The results demonstrate the effectiveness of COI metabarcoding in verifying honey authenticity and highlight the predominance of C-lineage honey bees in the production of commercial honeys from northwestern Europe. This finding suggests a limited presence of the native M-lineage ancestry, underscoring the need for conservation efforts.